Concept of Quantitative Research Methodology and Its Implications on Methods in Islamic Education - Afriana, Santy; Rahmaniar, Erita; Shaleh, Shaleh (Universitas Muhammadiyah Mataram, 2022)
In the world of educators, it is inseparable from research carried out as an effort to find the truth or to find out something new by collecting, processing, and analyzing data using data analysis methods that are in accordance with the type of research. The purpose of this study is to describe the concept of quantitative research methods and their interactions in Islamic education research. The method in this type of research uses literature on the descriptive-analytical literature method. This study uses data analysis techniques, namely the content analysis method (Content Analysis) to obtain valid and reproducible references based on the context. The results of the study show a correlation between quantitative concepts and the concept of Islamic education, namely the experimental method and the tajribi method which have similarities, but in tajribi a systematically planned plan in finding facts or symptoms based on Islamic teachings guided by the Qur'an and Hadith.